2007
DOI: 10.1002/art.22301
|View full text |Cite
|
Sign up to set email alerts
|

Sex and ethnic differences in the association of ASPN, CALM1, COL2A1, COMP, and FRZB with genetic susceptibility to osteoarthritis of the knee

Abstract: Objective. To assess whether the association of genetic polymorphisms with osteoarthritis (OA) in other populations could be replicated in a large, multicenter, mixed-sex, case-control study of clinical knee OA.Methods. Genetic polymorphisms in OA candidate genes were genotyped in 298 men and 305 women, ages 50-86 years, all of whom had a diagnosis of knee OA as assessed clinically and radiographically, and in 300 male and 299 female control subjects matched for age and ethnicity. Allele and haplotype frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
0
10

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(143 citation statements)
references
References 33 publications
(38 reference statements)
9
124
0
10
Order By: Relevance
“…Our data apply only to women of European descent. Differences in the strength or even the presence of genetic associations with OA between sexes have previously been reported, as have those between Asian and Caucasian patients (27,28); therefore, it is possible that this gene may not be associated with OA in men or in other ethnic groups.…”
Section: Discussionmentioning
confidence: 97%
“…Our data apply only to women of European descent. Differences in the strength or even the presence of genetic associations with OA between sexes have previously been reported, as have those between Asian and Caucasian patients (27,28); therefore, it is possible that this gene may not be associated with OA in men or in other ethnic groups.…”
Section: Discussionmentioning
confidence: 97%
“…The identification of such genes should be considered essential to obtain a better understanding of OA and the underlying biologic events preceding its onset (3). One path leading to OA in which genes might play a role starts with the causal effect of hip morphology on the development of OA and may explain part of the heritability of hip OA.…”
mentioning
confidence: 99%
“…36 When multiple testing is considered, only a negative association has been reported in replication studies, even in the European Caucasians. 13,37,38 We also did not find an association of the FRZB variants in the Japanese and Han Chinese populations (D Shi et al, unpublished data). Taken together with the lack of functional characterization of the FRZB polymorphisms and evidence of causality in OA, the previously reported FRZB association 36 seems to be just another example of a false-positive association.…”
Section: Gdf5mentioning
confidence: 69%
“…However, replication studies in the European Caucasian and Chinese populations reported negative associations for this SNP (rs12885713). [12][13][14][15] Using the same system, Miyamoto et al 16 identified association of DVWA (double von Willebrand factor type A domain) with knee OA. DVWA was a previously unknown gene, not in the gene database.…”
Section: Gwas Of Oamentioning
confidence: 99%